Реалізація політики сталого еколого-економічного розвитку в країнах ЄС: досвід для України - Грабинський, І. М.; Федунь, Ю. Б. (Видавництво Львівської політехніки, 2010)
Досліджуються шляхи та етапи реалізації політики сталого еколого-економічного розвитку країн ЄС та можливість використання їхнього досвіду для України. Ways and implementation of policy of the sustainable ekological-economic development of countries of EU and possibility of the use of their experience for Ukraine are explored.
The policy implementation of sustainable environmental-economic development in eu countries: experience for Ukraine
Keywords: концепція сталого розвитку; економічний розвиток; екологічна безпека; етапи реалізації політики сталого еколого-економічного розвитку країн ЄС; стратегічні цілі; sustainable development concept; economic development; environmental safety; the stages of policy implementation of sustainable environmental-economic development in EU countries; strategic goals